Analisis Dampak Lingkungan Produksi Tahu dengan Pendekatan Life Cycle Assessment - Eli Masidah; Sukarno Budi Utomo (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. The tofu industry is a Small and Medium Enterprise (SME) sector that plays an important role in providing food for Indonesian communities; however, it is characterized by relatively high water and energy consumption. In micro-scale SMEs, production processes are generally carried out using traditional methods without standardized operational parameters, which may lead to inefficient resource utilization and increased environmental burdens. This study aims to evaluate operational efficiency and identify environmental hotspots in micro-scale tofu production with a capacity of 3 kg of soybeans per production cycle. The method employed was Life Cycle Assessment (LCA) using a gate-to-gate system boundary based on the ISO 14040 standard. Inventory analysis was conducted throughout a 7-hour production process, covering the stages of washing, soaking, grinding, cooking, filtering, and coagulation. The results showed that processing 3 kg of soybeans required 90 liters of water, resulting in a water-use ratio of 30:1, and generated a Global Warming Potential (GWP) of 5.57 kg CO₂-equivalent emissions. The cooking stage was identified as the primary environmental hotspot, contributing 94.1% of total emissions due to the use of firewood as fuel, while the highest water consumption occurred during the cooking and filtering stages. Therefore, the adoption of more efficient fuel sources and the implementation of water circularity management are recommended to reduce environmental impacts and improve the sustainability of tofu production. Abstrak. Industri tahu merupakan sektor Industri Kecil Menengah (IKM) yang berperan penting dalam penyediaan pangan masyarakat Indonesia, namun memiliki intensitas penggunaan air dan energi yang relatif tinggi. Pada IKM skala mikro, proses produksi umumnya masih dilakukan secara tradisional tanpa parameter operasional yang terstandarisasi sehingga berpotensi menimbulkan inefisiensi penggunaan sumber daya dan meningkatkan beban lingkungan. Penelitian ini bertujuan untuk mengevaluasi efisiensi operasional serta mengidentifikasi titik kritis (hotspot) lingkungan pada produksi tahu skala mikro dengan kapasitas 3 kg kedelai per siklus produksi. Metode yang digunakan adalah Life Cycle Assessment (LCA) dengan batas sistem gate-to-gate berdasarkan standar ISO 14040. Analisis inventori dilakukan pada proses produksi selama 7 jam yang mencakup tahapan pencucian, perendaman, penggilingan, pemasakan, penyaringan, dan koagulasi. Hasil penelitian menunjukkan bahwa pengolahan 3 kg kedelai membutuhkan 90 liter air dengan rasio penggunaan air sebesar 30:1 dan menghasilkan emisi Global Warming Potential (GWP) sebesar 5,57 kg CO₂ ekuivalen. Tahap pemasakan menjadi hotspot utama dengan kontribusi emisi sebesar 94,1% akibat penggunaan kayu bakar, sedangkan konsumsi air terbesar terjadi pada tahap pemasakan dan penyaringan. Oleh karena itu, penerapan bahan bakar yang lebih efisien serta pengelolaan sirkularitas air direkomendasikan untuk mengurangi dampak lingkungan dan meningkatkan keberlanjutan produksi tahu.